Наречия в удмуртском языке: [монография] / А. А. Шибанов ; [научный редактор Л. Е. Кириллова] - Шибанов Алексей Александрович (УрО РАН, 2012)
Экземпляры: кр (20170321) / Инвентарный номер: 42210 / Цена: / Сис.шифр: 81.2 (2Рос-Удм) / Авт.знак: Ш 55 / ГРНТИ: 16 / ББК: 81.2 (2Рос-Удм)